2011
DOI: 10.1007/s11033-011-0853-8
|View full text |Cite
|
Sign up to set email alerts
|

The restoration of full-thickness cartilage defects with mesenchymal stem cells (MSCs) loaded and cross-linked bilayer collagen scaffolds on rabbit model

Abstract: Cartilage has a limited self-repair capability and the repair of large cartilage defects remains a challenge in clinic. This study aimed to investigate the effect of mesenchymal stem cells (MSCs) loaded three-dimensional bilayer collagen scaffold for cartilage repair. Cross-linked three-dimensional bilayer collagen scaffolds seeded with or without MSCs were implanted into large cartilage defects (4 mm in diameter; 3 mm in depth) in rabbit knees. The untreated cartilage defects served as control. The tissue res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 31 publications
2
27
0
2
Order By: Relevance
“…However, cartilage tissue engineering systems with either cell type have been shown to be successful in some cases and to different extents in various animal models (Grässel and Anders, 2012). Although large animal models (such as pigs, goats, and horses) may more closely resemble the human system, the herein used rabbit model is one of the well accepted small animal models for evaluation of GF or cell-loaded scaffolds in cartilage defects (Sellers et al, 1997;Sellers et al, 2000;Rudert, 2002;Shao et al, 2006;Holland et al, 2007;Qi et al, 2009;Im and Lee, 2010;Jiang et al, 2010;Tokuhara et al, 2010;Wang et al, 2010;Chen et al, 2011;Qi et al, 2011;Yang et al, 2011;Qi et al, 2012;Zhang et al, 2013). Additional to the choice of an adequate animal model, there are still a number of challenges to be overcome in the search for optimum cartilage repair conditions as e.g., the recognition of the optimal cell source, scaffolds, and GFs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, cartilage tissue engineering systems with either cell type have been shown to be successful in some cases and to different extents in various animal models (Grässel and Anders, 2012). Although large animal models (such as pigs, goats, and horses) may more closely resemble the human system, the herein used rabbit model is one of the well accepted small animal models for evaluation of GF or cell-loaded scaffolds in cartilage defects (Sellers et al, 1997;Sellers et al, 2000;Rudert, 2002;Shao et al, 2006;Holland et al, 2007;Qi et al, 2009;Im and Lee, 2010;Jiang et al, 2010;Tokuhara et al, 2010;Wang et al, 2010;Chen et al, 2011;Qi et al, 2011;Yang et al, 2011;Qi et al, 2012;Zhang et al, 2013). Additional to the choice of an adequate animal model, there are still a number of challenges to be overcome in the search for optimum cartilage repair conditions as e.g., the recognition of the optimal cell source, scaffolds, and GFs.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, scaffolds may be loaded with GFs such as bone morphogenetic protein (BMP)-2 and TGF-b1 (Sellers et al, 1997;Sellers et al, 2000;Holland et al, 2005;Holland et al, 2007;Reyes et al, 2012), seeded with chondrocytes or MSCs Qi et al, 2011;Ito et al, 2012), or employed with combinations of both GFs and cells (Im and Lee, 2010;Wang et al, 2010). To date, only few studies compare MSCs and chondrocytes in cartilage defect repair.…”
Section: Introductionmentioning
confidence: 99%
“…For implantation purposes in vivo, BMSC seeding densities of 1-50 × 10 6 cells/cm 3 of biomaterial matrix have been used in preclinical animal studies. 1,14,[23][24][25][26][27][28][29][30][31][32] In clinical studies, a density of 5 × 10 6 cells/cm 3 has been reported although the rationale for adopting this seeding density was not described. 3,4 The objective of this study was to assess the impact of cell seeding density within a clinically relevant, collagen I scaffold on in vitro BMSC chondrogenesis following 2D and 3D isolation and expansion.…”
Section: Introductionmentioning
confidence: 99%
“…27 Scaffolds that provide sufficient mechanical support at implantation reduce the need for extended culture periods before the repair surgery. The regenerated tissue would develop under physiological loading conditions, which may ideally provide better functional tissue.Another approach is to first precondition the cell-scaffold construct in vitro before implantation into the defect (e.g., [28][29][30][31][32] ). In vitro cultivation provides a controlled nutrient supply and loading environment that may be optimized for matrix synthesis to produce stiff cartilage-like constructs that may ideally sustain physiological loading following implantation.…”
mentioning
confidence: 99%